An Immature Dermapteran Misidentified as an Adult Zorapteran: The Case of Formosozoros newi Chao & Chen, 2000 - Kočárek, Petr; Hu, Fang-Shuo (Insects, 2023)
Zoraptera shows extreme uniformity in general body morphology, with the exception of Formosozoros (=Zorotypus) newi Chao & Chen, 2000, which stands out in terms of the shape and arrangement of its legs, the cerci, and several other morphological characters. After critical evaluation, we found that this species is not a zorapteran but is instead a nymph (1st instar) of an earwig; i.e., F. newi is a dermapteran. Because of the lack of morphological descriptions of Dermaptera nymphs that would allow species identification, and because the type material of F. newi is lost, a more detailed classification is not possible. We therefore propose that the genus name Formosozoros Chao & Chen, 2000 and the species name Formosozoros newi Chao & Chen, 2000 are nomina dubia.
Keywords: taxonomy; Oriental region; classification; Taiwan; Zorotypus; Polyneoptera